Managing Corporate Strategy from the Expansion Perspective - Dumitru-Alexandru BODISLAV; Florina BRAN; Mariana IOVIȚU (Revista de Management Comparat International, 2014)
This research paper tries to highlight what are the paths used by companies to develop their business model worldwide and what strategies they should approach in their chase to maximize their profits, market share or global connectivity towards clients. The authors try to bring upfront and objective the main components that make a company choose a path or another, starting from leadership, resources, market needs and their synergic result, the competitive advantage. The paper tries also to bring together economic reality and economic theory for the better value of both of them, making it work for the better good of the society, of the economy and especially by accelerating self interest and what motivates the people behind companies to develop better and better products and how they manage to do that.